Recent improvements in the Turkish Childhood National Immunization Program - Ceyhan, Mehmet (The Turkish Journal of Pediatrics, 2010)
The Childhood National Immunization Program (NIP) is a key element of the primary healthcare and plays a major role in the national health status. The Turkish NIP, which is run by the Ministry of Health, included mainly the basic vaccines (Bacillus Calmette-Guerin [BCG], diphtheria-pertussis-tetanus [DPT], polio, measles) until 2005. However, a change in the governmental policies in 2002 and a close collaboration with the Advisory Board of Immunization have improved the Turkish NIP not only in terms of the quality of the vaccines and vaccination rates but also the number of pathogens covered. Currently, Turkey has a NIP that is equivalent to or better than that of the other European countries. However, making vaccination a constant part and priority of the state health policies is necessary for sustainability. Political commitment and efficient multi-sectorial collaboration and awareness are crucial.